Pengaruh Penjualan, Total Hutang, Modal Kerja Terhadap Laba Bersih - Imelda Muntiara Putri; Matyani; Ashari Sofyaun (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The purpose of this study is to determine the effect of Sales, total debt, and working capital on net profit. The data used are existing data sources, both internal and external data that can be published. The data used are financial reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023 with a total of 96 data. The analysis method shows that partially sales and total debt do not affect net profit. Working capital has a positive effect on net profit.